2007
DOI: 10.1016/j.febslet.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminus of the yeast Lsm4p is required for the association to P‐bodies

Abstract: We previously reported that Saccharomyces cerevisiae mutants in mRNA decapping and mutants expressing a truncated form of the KlLSM4 gene, showed premature senescence and apoptotic phenotypes.Here, we show that this truncated protein is dispersed in the cytoplasm and does not assemble to P-bodies. As reported in decapping mutants, we observed an increase in the number of P-bodies suggesting that the truncation of the protein impairs this process. The number of P-bodies also increases after oxidative stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Interactions within prion-like domains of some RNP granule components might be important for formation of P-bodies and neuronal RNP granules (Decker et al, 2007;Mazzoni et al, 2007;Reijns et al, 2008;Salazar et al, 2010). Mechanisms involved in RNP granule assembly in the nematode germline include hydrophobic interactions between the phenylalanine-glycine repeat domains of VASA-related proteins GLH-1/2/4 (Updike et al, 2011), and self-interaction domains of P-granule abnormality family member (PGL) proteins (Hanazawa et al, 2011).…”
Section: Planarian Chromatoid Body Structurementioning
confidence: 98%
“…Interactions within prion-like domains of some RNP granule components might be important for formation of P-bodies and neuronal RNP granules (Decker et al, 2007;Mazzoni et al, 2007;Reijns et al, 2008;Salazar et al, 2010). Mechanisms involved in RNP granule assembly in the nematode germline include hydrophobic interactions between the phenylalanine-glycine repeat domains of VASA-related proteins GLH-1/2/4 (Updike et al, 2011), and self-interaction domains of P-granule abnormality family member (PGL) proteins (Hanazawa et al, 2011).…”
Section: Planarian Chromatoid Body Structurementioning
confidence: 98%
“…In addition, in metazoans, depletion of microscopically visible P-bodies does not seem to affect miRNA-mediated repression, decay of messages containing ARE elements, or decay of transcripts subject to NMD (Chu and Rana 2006;Stoecklin et al 2006;Eulalio et al 2007b). In contrast, deletion of the Lsm4 carboxy-terminal domain, which promotes Pbody assembly (Decker et al 2007;Mazzoni et al 2007;Reijns et al 2008), can affect mRNA degradation in at least some strains and/or conditions (Reijns et al 2008), which suggests that aggregation of individual mRNPs into larger structures may have some role in mRNA degradation. In addition, there is some evidence that P-body aggregation may play a role in the long-term survival of yeast cells during stationary phase (Ramachandran et al 2011).…”
Section: Why Do Mrnps Aggregate?mentioning
confidence: 99%
“…P-bodies are then formed from these individual mRNPs aggregating into larger structures. In yeast, aggregation of mRNPs into P-bodies has been shown to be primarily dependent on a self-interaction domain (referred to as a Yjef-N domain) in the Edc3 protein and a glutamine/asparagine (Q/N) rich prion-like domain in the Lsm4 carboxyl terminus (Decker et al 2007;Mazzoni et al 2007;Reijns et al 2008). Because the YjeF domain of Edc3 is conserved (Ling et al 2008), it is likely that Edc3 will contribute to assembly of metazoan Pbodies.…”
Section: How Do Cytoplasmic Mrnp Granules Assemble?mentioning
confidence: 99%
“…This may be explained by the targeting of mRNAs to stress granules, which are thought to act as storage factors that sort mRNAs for degradation or later translation following the relief of stress conditions (Teixeira et al 2005). Storage or degradation of mRNAs in P bodies and stress granules may play an important role in regulating gene expression during oxidative stress conditions since it has been shown that the number of P bodies is significantly increased following UV and hydrogen peroxide stress (Teixeira et al 2005;Mazzoni et al 2007). …”
Section: Cellular Responses To Rosmentioning
confidence: 99%